POLYCYCLIC FORMATION OF PLATINUM GROUP MINERALS FROM PLACERS OF THE URAL AND TIMAN RANGES - Kostoyanov A.I.; Ivanov D.Yu.; Manoilov V.V. (My University, 2003)
This paper discusses the osmium isotopic composition of platinum group minerals (PGM)in placers related to gabbroic-ultrabasic plutons of the Polar, Nether-Polar, and Central Ural and Timan Ranges. Our isotopic data obtained by the mass spectrometry of electronegative ions (NTIMS) are compared with data on the osmium isotopic composition of PGM in lode and placer deposits of other platinum-bearing regions in Russia and abroad. The osmium isotopic composition of PGM (187Os/ 188Os) varies in placers, with the limiting values being typical of the mantle (chondrites), which allowed us to calculate the model Re-Os age of single PGM grains. Statistical data on the ages show several stages of PGM formation, coincident with the periods of tectonic-magmatic rejuvenation of the Ural and Timan ranges. The average cycle of PGM formation is estimated at about 200 m.y., which is comparable with the formation periodicity of hot spots at the mantle-core boundary studied by N.L. Dobretsov and A.G. Kirdyashkin. The studied variations in the osmium isotope composition suggest a mantle-metasomatic genesis of PGM and are more consistent with the concept that ultrabasites were solid-plastic when transported to the Earth's crust.